High carotenoids content can enhance resistance of selected Pinctada fucata families to high temperature stress. Issue 61 (February 2017) - Meng, Zihao; Zhang, Bo; Liu, Baosuo; Li, Haimei; Fan, Sigang; Yu, Dahui
Abstract: Carotenoids are a class of natural antioxidants widely found in aquatic, and they have significant effects on the growth, survival, and immunity of these organisms. To investigate the mechanisms of carotenoids in high temperature resistance, we observed the immune response of selected pearl oyster Pinctada fucata (Akoya pearl oyster) families with different carotenoids contents to high temperature stress. The results indicated that the survival rate (SR) of P. fucata decreased significantly with increase in temperature from 26 °C to 34 °C and with the decrease of total carotenoids content (TCC); when the TCC was higher, the SR tended to be higher. TCC and total antioxidant capacity (TAC) decreased significantly at 30 °C with increasing stress time. Correlation analysis indicated that TAC was positively and linearly correlated with TCC, and SR was S-type correlated with TCC and TAC. Immune analysis indicated that levels of superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA) in selected families (with higher TCC) under temperature stress (at 30 °C) were generally significantly lower than in the control group (with lowest TCC) and from 0 to 96 h, the levels of each of these substances varied significantly. Levels of SOD, CAT, and MDA within each family first rose from 0 to 3 h, then decreased to their lowest point after 24 h, and then rose again to their highest levels at 96 h. When TCC was higher, the levels of SOD, CAT, and MDA tended to be lower. These findings indicated that carotenoids play an important role in improving survival rates of P. fucata under high temperature stress by enhancing animals' antioxidant system, and could serve as an index for breeding stress-resistant lines in selective breeding practices. Highlights: Indexes to selectively breed high temperature resistance in shellfish are proposed. Antioxidant enzymes had low activity in the presence of carotenoids. High temperature stress in Pinctada fucata might be mitigated by carotenoids.